Acute exacerbation of rheumatoid arthritis–associated interstitial lung disease: clinical features and prognosis - Izuka, Shinji; Yamashita, Hiroyuki; Iba, Arisa; Takahashi, Yuko; Kaneko, Hiroshi (Rheumatology (Oxford, England), 2021)
Abstract Objectives RA-associated interstitial lung disease (RA-ILD) is commonly associated with acute exacerbations (ILD-AE). This study examined the clinical characteristics and risk factors of ILD-AE and mortality of RA-ILD. Methods We retrospectively collected data on 165 RA-ILD patients who visited or were admitted to our hospital between January 2007 and December 2019. We compared the clinical characteristics of patients who did and did not develop ILD-AE and identified variables significantly associated with ILD-AE. We also compared the admission characteristics of those who survived and those who died after admission for ILD-AE. ILD-AE was defined using previously proposed criteria, modified slightly for application to RA-ILD. Results The mean patient age was 73.6 years (s.d. 9.7) and 97 (71.9%) patients were female. Thirty (22.2%) patients developed ILD-AE, 13 (43.3%) of whom died. In univariate analyses, neither the usual interstitial pneumonia (UIP) pattern nor MTX was associated with ILD-AE. In multivariate analyses, the UIP pattern was significantly associated with ILD-AE [odds ratio (OR) 2.55 (95% CI 1.05, 6.20), P = 0.038]. In the Cox proportional hazards model, the UIP pattern [hazard ratio (HR) 4.67 (95% CI 1.02, 21.45), P = 0.048] was significantly associated with death, while MTX use [HR 0.16 (95% CI 0.04, 0.72), P = 0.016] was significantly associated with survival. Conclusion Our data suggest that the UIP pattern is related to ILD-AE. Furthermore, both the UIP pattern and non-use of MTX might be related to death from ILD-AE in RA-ILD.